Los rendimientos de la educación en México - Eduardo Morales-Ramos (Banco de México, 2011)
– This paper estimates private returns to education in Mexico by means of the Mincer model. The natural ability bias that the literature reports in this type of estimations is tried to be solved using the control function method. Through this method some variables relevant to wage determination are included in the model, such as natural ability index, mother's education, household infrastructure, height and health. Results suggest that the returns to education by year of schooling in Mexico are between 8.2% and 8.4 %. On the other hand, results by level of education suggest that more education is associated with higher returns. The highest return to education in both absolute and relative terms is provided by Postgraduate education followed by Graduate education. In general, results suggest that there is a convex relationship between education level and wage.
Keywords: I21; J24; J31; 330; private returns to education; natural ability bias; natural ability index; mother's education; Mexico; Bildungsertrag; Frauenbildung; Mütter; Bildungsverhalten; Mexiko